Effective intervention characteristics of a doping prevention program for athletes: A systematic review with meta-analysis - Reynoso-Sánchez, L. F.; Molgado-Sifuentes, A.; Muñoz-Helú, H.; López-Walle, J. M.; Soto-García, D. (Sports, 2025)
This study systematically reviewed the effectiveness of cognitive, affective, and combined approaches in doping prevention, considering the impact of athletes` active versus passive participation. Following the PRISMA 2020 guidelines and the PICOS framework, a literature search identified ten studies involving 3581 athletes (1094 women, 2487 men). Ten studies were included as a sample in the meta-analysis and meta-regression, which were used in the effect size calculation. This meta-analysis shows that anti-doping education programs effectively improve short-term doping intentions (ES = 0.29, p < 0.001) and anti-doping behaviors (ES = -0.27, p < 0.001), although there is a decline in the long-term effects (ES = -0.13, p = 0.009). Moral behaviors were unaffected (ES = 0.01, p < 0.001), suggesting that changing deeper values requires alternative approaches like mentorship. Passive participation negatively impacted doping intentions (ES = -0.40, p = 0.004) and behaviors (ES = -0.40, p = 0.022), highlighting the need for active engagement. Pre-experimental designs showed a negative effect on behaviors (ES = -0.74, p = 0.023), emphasizing the importance of rigorous methodologies. While anti-doping education programs effectively influence short-term attitudes and intentions, sustaining behavioral change requires continuous reinforcement and active engagement. The decline in the long-term effects suggests that standalone interventions are insufficient to instill lasting anti-doping behaviors in athletes.